PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DENGAN METODE APIQ (ARITMATIKA PLUS INTELIGENSI QUANTUM) PADA MATERI FPB DAN KPK DI KELAS V MI ISLAMIYAH SIMOREJO KEPOHBARU BOJONEGORO TAHUN PELAJARAN 2014/2015 - Laili, Nur Hidayati; Wijayanti, Sulistiya (Universitas Islam Darul Ulum, 2016)
In a cooperative learning model Think Pair Share (TPS), there are three stages, namely Think (think), Pair (pair) and Share (share). While the method APIQ (Arithmetic Plus Intelligence Quantum) is a learning method that helps students solve mathematical problems with the strategy and the whole process of learning to sharpen the understanding and memory, as well as helping students understand math concepts in a creative and fun. The problems in this study is whether the cooperative learning model Think Pair Share (TPS) Method APIQ (Arithmetic Plus Intelligence Quantum) effectively applied to the material FPB and the Commission in terms of (1) the students activity, (2) the teacherâs activities, (3) the studentsâ response, (4) the mastery learning in class V MI Islamiyah Simorejo Kepohbaru Bojonegoro in the academic year of 2014/2015. The subjects of this study were students of class V MI Islamiyah Simorejo Kepohbaru Bojonegoro in the academic year of 2014/2015, in sum of 17 students. While in the observation only 8 students and a researcher as a teacher who observed the activity. Data collection methods used were observations, questionnaires and tests. From the observation of student activity obtained positive activities students of 94.64%, from observations of the teachers activities obtained positive activity teacher of 98.21%, from the student questionnaire responses obtained positive responses of students of 91.18%, and the results of data analysis test students mastery learning students obtained classically of 88.23%. Based on the results of research that has been carried out, it can be concluded that the application of cooperative learning model Think Pair Share (TPS) method APIQ (Arithmetic Plus Intelligence Quantum) effectively applied to the material FPB and the Commission in class V MI Islamiyah Simorejo Kepohbaru Bojonegoro in the academic year of 2014 / 2015.